Influenza pandemic preparedness: motivation for protection among small and medium businesses in Australia - MacIntyre C Raina; Donovan Robert J; Cooke Feonagh C; Watkins Rochelle E; Itzwerth Ralf; Plant Aileen J (BMC, 2007)
Abstract Background Community-wide preparedness for pandemic influenza is an issue that has featured prominently in the recent news media, and is currently a priority for health authorities in many countries. The small and medium business sector is a major provider of private sector employment in Australia, yet we have little information about the preparedness of this sector for pandemic influenza. This study aimed to investigate the association between individual perceptions and preparedness for pandemic influenza among small and medium business owners and managers. Methods Semi-structured face-to-face interviews were conducted with 201 small and medium business owners or managers in New South Wales and Western Australia. Eligible small or medium businesses were defined as those that had less than 200 employees. Binomial logistic regression analysis was used to identify the predictors of having considered the impact of, having a plan for, and needing help to prepare for pandemic influenza. Results Approximately 6 per cent of participants reported that their business had a plan for pandemic influenza, 39 per cent reported that they had not thought at all about the impact of pandemic influenza on their business, and over 60 per cent stated that they required help to prepare for a pandemic. Beliefs about the severity of pandemic influenza and the ability to respond were significant independent predictors of having a plan for pandemic influenza, and the perception of the risk of pandemic influenza was the most important predictor of both having considered the impact of, and needing help to prepare for a pandemic. Conclusion Our findings suggest that small and medium businesses in Australia are not currently well prepared for pandemic influenza. We found that beliefs about the risk, severity, and the ability to respond effectively to the threat of pandemic influenza are important predictors of preparedness. Campaigns targeting small and medium businesses should emphasise the severity of the consequences to their businesses if a pandemic were to occur, and, at the same time, reassure them that there are effective strategies capable of being implemented by small and medium businesses to deal with a pandemic.